New technologies: a brief introduction / Muhammad Hariz Hamid - Hamid, Muhammad Hariz (Faculty of Accountancy, 2021)
In recent years, technology has become increasingly diverse and advanced – having significant impacts on society. It has not only ingrained in our daily lives, but also transformed the way we do businesses by introducing new approaches, techniques, and tools. As a result of the emergence of new technologies, for example, business processes have now become more integrated and streamlined. To have a clear idea of this evolution, the remainder of this article will give us a taste of what these new technologies are all about. One of the most popular emerging technologies today is the blockchain technology. A "blockchain" is a collection of records that are linked together. It is also known as distributed ledger technology (DLT), which involves entering and storing records in a distributed ledger and making them accessible to all relevant parties. This differs from traditional accounting which keeps all records in a centralized ledger, accessible to only accountants and auditors. Each record entered into the blockchain will be encrypted and verified by a large number of computers interconnected via the internet (Huang et al., 2021). Each entry will be automatically timed and stamped, and given a unique hash code. Any modifications to the original records will generate a new hash, with the old hash remaining in other blocks. This means that, if someone wishes to modify an accounting record, he will have to make sure that all chains have the same hash code.